The centrosome as potential target for cancer therapy and prevention - Korzeniewski, Nina; Hohenfellner, Markus; Duensing, Stefan (Expert opinion on therapeutic targets, 2013)
Introduction: Cancer initiation and propagation is not possible without cell division. Besides microtubules, which are targeted by taxanes as part of a number of standard chemotherapy regimens, mitosis depends on small cellular organelles known as centrosomes. Centrosome abnormalities are a common finding in tumors including major human malignancies such as prostate or breast cancer. Centrosome aberrations can drive chromosome missegregation and aneuploidy, thereby promoting malignant progression. Nonetheless, these important cellular structures have not yet been directly exploited for targeted interventions. Areas covered: This review will summarize the current knowledge of normal and aberrant centrosome duplication. We will highlight the principal pathways leading to aberrant centrosome numbers and the evidence for a role of centrosome amplification in malignant progression. Strategies to target centrosome-mediated cell division errors will be discussed. Lastly, we will review the evidence for centrosome clustering as a druggable cellular process. Expert opinion: Recent advances in the understanding of centrosome biogenesis have revealed a number of potential centrosomal drug targets including Polo-like kinases, Cyclin-dependent kinases, Aurora kinases, and molecular motor proteins. For some of these proteins, targeted inhibitory compounds are available and in vitro experiments have provided the proof-of-concept that blocking centrosome overduplication can result in a reduction of aneuploid cells. In addition, inhibition of centrosomal clustering has antitumor activity in vitro and in vivo. Nonetheless, further in vitro and preclinical studies are required to determine the most effective way to exploit the centrosome for therapeutic or preventive anticancer strategies.
Gesehen am 20.11.2018
Published online: 15 Oct 2012